The Effect of Financial Literacy, Financial Attitude, Locus of Control, and Lifestyle on Financial Management Behavior (Case Study on Undergraduate Accounting Study Program Students Faculty of Economics and Business Jambi University) - Anastasya Laga; Achmad Hizazi; Yuliusman (Indonesian Journal of Economic & Management Sciences, 2023)
This study aims to see how financial literacy, financial attitude, locus of control, and lifestyle influence financial management behavior. For data analysis using a questionnaire, the sample of 100 respondents was chosen using a purposive sampling technique. Using SPSS For Windows Version 26 software, the multiple linear regression analysis approach was used to evaluate the hypothesis. The findings in this study are that financial literacy, financial attitude, locus of control, and lifestyle have a positive and significant influence on financial management behavior. Partially, financial literacy and lifestyle have a positive influence on financial management behavior, while financial attitude and locus of control have no effect on financial management behavior